Biosurfactant production by Mucor circinelloides: Environmental applications and surface‐active properties. Issue 5 (22nd February 2018) - Hasani zadeh, Parvin; Moghimi, Hamid; Hamedi, Javad
Abstract: Biosurfactants are structurally a diverse group of surface‐active molecules widely used for various purposes in industry. In this study, among 120 fungal isolates, M‐06 was selected as a superior biosurfactant producer, based on different standard methods, and was identified as Mucor circinelloides on the basis of its nucleotide sequence of the internal transcribed spacer (ITS) gene. M. circinelloides reduced the surface tension to 26 mN/m and its EI24 index was determined to be 66.6%. The produced biosurfactant exhibited a high degree of stability at a high temperature (121°C), salinity (40 g/L), and acidic pH (2–8). The fermentation broth's ability to recover oil from contaminated sand was 2 and 1.8 times higher than those of water and Tween 80, respectively. The ability of biosurfactant to emulsify crude oil in the sea and fresh water was 64.9 and 48% respectively. This strain could remove 87.6% of crude oil in the Minimal Salt Medium (MSM) crude oil as the sole carbon source. The results from a primary chemical characterization of crude biosurfactant suggest that it is of a glycolipid nature. The strain and its biosurfactant could be used as a potent candidate in bioremediation of oil‐contaminated water, soil, and for oil recovery processes.